Pengaruh Profitabilitas Dan Aktivitas Terhadap Pertumbuhan Perusahaan Yang Terdaftar Di Jakarta Islamic Index (JII) - Yolanda, Agnes (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2021)
The purpose of this study is to determine how much influence Net profit margin and total assets turnover on the growth of companies listed on the Jakarta Islamic Index partially and simultaneously. This research uses an associative quantitative approach. The data analysis technique used in this study is multiple linear regression. The results showed that net profit margin and total asset turnover had a significant effect with the sig value (0.032) <α (0.05), while partially the net profit margin had a significant effect with the sig value (0.035) <α (0.05), whereas Total asset turnover has no significant effect on the sig value (0.812)> α (0.05), and the magnitude of the effect of net profit margin and total asset turnover on company growth is 0.092 or (9.2%), while the rest is 90.8%. influenced by other factors outside the research.